The application of kenikir (Cosmos caudatus) extract cream to inhibit the increase of melanin counts in the skin of guinea pigs (Cavia porcellus) exposed to ultraviolet B - Olivia Olivia; I Gusti Made Aman; AAGP Wiraguna (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2021)
Introduction: Hyperpigmentation is caused by the increase of melanin in the skin layer, especially the epidermal layer. Kenikir (Cosmos Caudatus) is a plant that can be used as an antioxidant and anti-melanogenic. The aim of this research was to prove the effectiveness of the cream with 4% kenikir (Cosmos Caudatus) extract to inhibit the increase of melanin in the skin of guinea pig (Cavia porcellus) exposed to ultraviolet B. Methods: The kenikir (Cosmos Caudatus) that have been extracted in Food Laboratory of Agriculture Faculty in Universitas Udayana became the main requirement in this research. This research employed an experimental design with post-test only control group method. To conduct this study, 36 male guinea pigs (Cavia porcellus), local strain, aged 3 months with 300-350mg body weight divided into 2 groups, each of which was 18. The duration of irradiation was 3 times a week with a total irradiation dose of 65 mJ/cm2. After 2 weeks of research, then the back skin tissue of guinea pigs biopsied as the histological preparations and then the Masson-Fontana staining was performed. The results were analyzed by using descriptive analysis, the test of normality and homogeneity and also independent t-test. Results: The control group (P0) (20,57±2,90%) had a bigger average melanin count than the treatment group (P1) (1,41±0,437%) significant statistically (p<0.001). Conclusion: this research is the cream with 4% of kenikir (Cosmos Caudatus) extract can inhibit the increase of melanin counts in the skin of a male guinea pig (Cavia porcellus) exposed to Ultraviolet B.